Prospects of Rice Husk Gasification for Power Generation in Bangladesh - Das, Barun Kumar; Mustafi, Nirendra Nath; Hoque, S.M. Najmul (Journal of Technology Innovations in Renewable Energy, 2013)
Electricity is the basic requirement to promote socio-economic development. In recent years, Bangladesh is facing severe power crisis all over the country, but the rural areas are the most vulnerable. This acute electricity crisis along with the conventional fuel crunch is affecting every sector of the country and economy is being crippled. To reduce the dependency on fossil fuels, rice husk which are widely abundant agricultural waste from rice industry could play a vital role in this regards. Bangladesh is an agricultural country and produces huge quantity of rice every year. In the year 2011, the total rice production was around 50.63 million tones. Husk is the waste biomass produce during the rice processing, on average it accounts around 20% of the rice produced on weight basis (10.12 million tones). The potential of power generation from rice husk by gasification is around 310 MWe in Bangladesh. The power plant to be installed near the large rice mills `cluster areas’ in Dinajpur, Bogra, Naogaon, Chapainawabganj and Ishwardi with the surplus rice husk. This paper consolidates information from various studies on the availability of rice husk, its characterization and estimates possible power potential that can be realized.